3D Seismic Sedimentology of Nearshore Subaqueous Fans – A Case Study from Dongying Depression, Eastern China - Fengli, Yang; Wenfang, Zhao; Zhuan, Sun; Haisheng, Cheng; Yunxin, Peng (IntechOpen, 2011)
None